Pragmatic awareness in university students: psychometric analysis of the CCP Questionnaire in Medellín, Colombia - Zambrano-Cruz, Renato; Guzmán Cabreja, Deisy Stefany; Meneses Giraldo, Laura Vanesa (Pensando Psicología, 2025)
Introduction. Pragmatic awareness (PA) is a critical and self-reflective ability that allows individuals to adapt their communication to different contexts. This skill contributes to successful human interaction by facilitating the understanding of implicit meanings and cultural norms. Despite its relevance, its psychometric properties and internal structure have not been validated in Hispanic-speaking university students in Latin America. Objective. To determine the psychometric properties of the Pragmatic Awareness Questionnaire (PAQ) in a sample of university students in Medellín, Colombia. Method. This is a quantitative, cross-sectional, instrument-based study using confirmatory and exploratory factor analysis, which evaluates the factor structure of the PAQ, its fit indices, and internal reliability in a sample of 423 university students from Medellín (68.08% female, 31.9% male), aged 18 to 40. Results. The model showed a good fit (CFI = 0.910; RMSEA = 0.067). The factor structure identified three factors; however, some items did not load on any of these factors, as they presented communality values between 0.735 and 0.593. Reliability was high for factors 1 (ω = 0.841) and 3 (ω = 0.811), and acceptable for factor 2 (ω = 0.625).Conclusions. The results support the use of the PAQ to assess pragmatic awareness in university students in Medellín, confirming a three-dimensional structure with good fit and acceptable reliability. However, items with no significant factor loading were identified, suggesting the need for revision to optimize their clarity and validity.
Keywords: Pragmatic awareness; Pragmatics; Interactive communication; Psychometrics